Some Main Results of Commissioning of The Dalat Research Reactor with Low Enriched Fuel - Nguyen , Nhi Dien; Luong , Ba Vien; Pham , Van Lam; Le , Vinh Vinh; Huynh , Ton Nghiem; Nguyen , Kien Cuong; Nguyen , Minh Tuan; Nguyen , Manh Hung; Pham , Quang Huy; Tran , Quoc Duong; Vo Doan , Hai Dang; Trang , Cao Su; et al. (Nuclear Science and Technology, 2014)
After completion of design calculation of the Dalat Nuclear Research Reactor (DNRR) for conversion from high-enriched uranium fuel (HEU) to low-enriched uranium (LEU) fuel, the commissioning programme for DNRR with entire core loaded with LEU fuel was successfully carried out from 24 November 2011 to 13 January 2012. The experimental results obtained during the implementation of commissioning programme showed a good agreement with design calculations and affirmed that the DNRR with LEU core have met all safety and exploiting requirements.